107 Enhanced endothelial cell coverage on graphene coated stents. (June 2018) - Jafarzadeh, Fatemeh; McManus, Daryl; Barbolina, Irina; Kostarelos, Kostas; Malik, Nadim; Casiraghi, Cinzia; Holt, Cathy M
Abstract : Introduction: Coronary artery disease is the leading cause of death worldwide. Stent implantation is performed widely to revascularise stenosed coronary arteries. Restenosis is a significant complication associated with bare metal stents (BMS). Drug eluting stents with adjunct anti-platelet therapy significantly improved restenosis risk but introduced late in stent thrombosis. Therefore, there remains a need for more effective coronary artery stents and the aim of this study is to improve currently available BMSs. Graphene is a 2D material consisting of a layer of hexagonal structured carbon atoms, exhibiting unique properties, ideal for implantable device coatings: it forms an impermeable membrane, is atomically smooth and has a Daruyhigh surface to volume ratio. We have coated currently available BMSs with graphene-based materials to enhance re-endothelialisation and hinder the formation of intimal hyperplasia resulting from possible aetiologies such as metal leaching or inflammatory reaction to the metal itself. Methods: Graphene-based bare metal stent coatings were optimised by investigating several coating methods. Human coronary artery endothelial cells (HCAECs) were cultured on control and coated stents. Cells were fixed at day 0 and day 8 post-seeding, followed by Hoechst 33 342 and Phalloidin staining for viewing under the fluorescence microscope. Subsequently, HCAEC number per mm2 area of stent was determined at both day 0 and day 8, and the difference calculated. One-Way ANOVA with multiple comparison was performed and p<0.05 considered as statistically significance. Results are shown as mean± SEM. Results: A spray coating method was selected for providing optimal coverage of graphene-based coating on BMSs. HCAEC count/mm2 was significantly more on the Graphene-based coating of the bare metal stent (1085±156 HCAEC count/mm2) compared to the uncoated control bare metal stent (486±130 HCAEC count/mm2) p=0.0063, n=3. Conclusion: An optimised prototype of graphene-based BMS coating was produced for preclinical evaluation. Increased HCAEC count per mm2 of graphene-based coated BMS was observed in comparison to the uncoated bare metal stents. These data provide the first indication of the potential feasibility of graphene-based materials as coatings on implantable coronary artery stents.